The Divergence of Divorce on the Divorcees Children in Tehsil & District Malakand, Khyber Pakhtunkhwa (Pakistan) - Muhammad Asghar Khan; Fazal Amin; Samina Bibi; Asad Ullah Khan; Wasiq Ahmad (Review Journal of Social Psychology & Social Works, 2025)
This research paper is based on the divergence of divorce on the divorcees’ children in district Malakand, Khyber Pakhtunkhwa, Pakistan. A sample size of 130 respondents (divorcee) from the total population 600 was randomly selected from the three purposively selected union councils from the universe. The data were analyzed through frequency distribution along with indexing all the variables and got them operational through Binary Response Model (Logistic Regression Analysis). At bi-variate level the effects of four independent variables (illiteracy, arranged marriage, early marriage and endogamy) were tested vide effects of divorce on children. The model proved statistically significant (Chi-square = 10, P= 0.040). The grouping variables and prediction variables had weak relationship (Nagelkerke’s R Square= 0.103). Moreover, 7 to 10 percent variations in effects of divorce on children were explained by grouping variables. Wald Test values showed only arranged marriage as significantly predicting effects of divorce on children (P=0.011). However, other variables (understanding meaning of divorce, early marriage and endogamy) were non-significant with relation to predicting effects of divorce on children. Exponential-β value for the arranged marriage was interpreted as; an increase in tendency towards arranged marriage increases the likelihood of negative effects of divorce on children by more than three times. The social stigmatization associated to divorce needs to be highlighted by religious scholars, highlighting provision of rights for both the genders to remarry specially for women folk, revisiting patriarchy in light of religion for equality of both genders and addressing the dilemma of owning of the divorcee children earlier to the division of marriage in terms of their asset to ownership rights along with the establishment of special treatment centers for the left over children to make them rehabilitate were some of the recommendations extended in light of study.